Selenium WebDriver 3 Practical Guide : End-To-end Automation Testing for Web and Mobile Browsers with Selenium WebDriver, 2nd Edition. - Gundecha, Unmesh (Packt Publishing Ltd, 2018)
Selenium WebDriver 3 is the latest version used by many professionals for automated testing. The book will guide you through various Selenium WebDriver APIs and provide solutions to the common challenges faced while using Selenium WebDriver. You will learn to use remote WebDriver to run tests on remote machines for cross-browser testing and ...